Review of Malaysian retail banking market: an industrial organizational perspective - Mohammed, Nafisah; Abdul Jalil, Suhaila (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2011)
The attempt of this paper is to analyze the Malaysian retail banking market within structure-conduct-performance paradigm framework which roots from the industrial organizational field. The Malaysian retail banking market practices dual banking system which consists of conventional and Islamic banking firms. Therefore, the analysis in this paper will focus on the structure, conduct and performance of both banking system descriptively. The structure of the retail banking market will also focused on several aspects such as market size and distribution, market competitiveness, market delineation and barriers to entry. While, marketing expenses, distribution of the branches and the quality of services will be analyzed to evaluate the banking firms conduct in the market. Meanwhile, the performance of the banking firms will be analyzed from two perspectives namely, ratio analysis and welfare perspectives. Overall, the study shows that both domestic and foreign banking firms play a significant role in the Malaysian retail banking market.